Evaluating professional practicums: possibility for the improvement of higher education in Mexico - Gutiérrez Bernal, Zayra Guadalupe (Consorcio de Universidades Mexicanas A.C., 2019)
According to the OECD (2019), higher education in Mexico must be better aligned with the changing needs of the economy. Almost half of employers warn of a lack of skills in their sector and consider that the education and training of job seekers is not sufficiently adequate to fulfill their needs. Professional practicums establish a link between higher education and the job market, such that, if interns’ work is aligned with the needs of employers, universities will have a better possibility of offering emerging professionals competencies required by the job market. One option is regulating and improving the system of professional practicums employed by institutions of higher education insofar as doing so has a great impact on the planning, execution, and results of programs offered by universities and favors the fulfillment of the primary functions of higher education. When there exists a discrepancy between the training of professionals and the needs of the job market, there is a need to identify what is happening with professional practicums. A literature review suggests that these practicums are not systematically evaluated. Prior to proposing such an evaluation, this article presents a series of reflections on practicum evaluation with the intent of supporting the proposal of a subsystem or an autonomous system of evaluation for professional practicums.